The indirect and direct effects of temperature and host plant resistance on population growth of soybean aphid (Aphis glycines) biotype 1 - Hough, Ashley Rose (Kansas State University, 2016)
Temperature has an important indirect impact on pest populations. Direct effects occur, but also may result from temperature-induced changes in plant quality, including the expression of host plant resistance traits. Therefore, I examined both indirect and direct effects of temperature on biotype 1 soybean aphids (SBA), Aphis glycines, on a Rag1-resistant soybean variety and compared the effects with a susceptible variety to gain a better understanding of how temperature impacts SBA. Four aphid responses were evaluated: preimaginal development, survival to adulthood, number of progeny produced, and adult longevity. In the first experiment, I grew soybean seedlings to the V-0 stage at 25°C and then conditioned them for 0, 3 or 5 days at 20° or 30°C before infesting with a single first instar SBA at each of the two experimental temperatures. Based on previous literature for SBA, I hypothesized that conditioning plants at the lower temperature would cause resistance to break down and that longer exposure would exacerbate the effect. Results showed that conditioning soybeans to 20°C significantly reduced SBA survival, and the effect on survival increased with longer conditioning. Conditioning plants to 30°C had no significant effect on SBA survival. However, estimated population growth decreased as conditioning time increased at 30°C and this effect was also observed at 20°C. Thus, plant resistance may have increased at both temperatures. The second experiment compared SBA responses, including population growth, at four temperatures (15, 20, 25, and 30⁰C) on a Rag1-resistant and susceptible soybean variety. I predicted that SBA fitness would be lower at all temperatures on resistant soybeans, but the magnitude of differences between cultivars would not be uniform across temperatures. Results indicated that both temperature (highest and lowest) and plant resistance detrimentally affected SBA fitness. There was also a significant interaction between the two variables with respect to SBA survival. Survival was lower and development rates were slower on the resistant cultivar. SBA required more degree-days to develop on resistant soybeans compared to the susceptible cultivar. This information will aid soybean producers in implementing a cost-efficient IPM strategy involving Rag1 resistant soybeans to combat SBA under a range of temperatures.
Keywords: Aphis glycines; soybean aphid; host plant resistance; Rag1; temperature effect; soybean